Correlation between microstructure and exothermic reaction kinetics of Al-CuO thermite nanocomposite powders fabricated by cryomilling - Oh, Minseok; Kim, Kwanil; Ahn, Byungmin (Archives of Metallurgy and Materials, 2019)
Al-CuO is a thermite material exhibiting the exothermic reaction only when aluminum melts. For wide spread of its application, the reaction temperature needs to be reduced in addition to the enhancement of total reaction energy. In the present study, a thermite nanocomposite with a large contact area between Al and CuO was fabricated in order to lower the exothermic reaction temperature and to improve the reactivity. A cryomilling process was performed to achieve the nanostructure, and the effect of composition on the microstructure and its reactivity was studied in detail. The microstructure was characterized using SEM and XRD, and the thermal property was analyzed using DSC. The results show that as the molar ratio between Al and CuO varies, the fraction of uniform nanocomposite structure was changed affecting the exothermic reaction characteristics.
Keywords: Cryomilling; High energy density materials; ITS applications; Nano-composite structure; Reaction characteristics; Reaction temperature; Thermite nanocomposites; Thermites; Al-CuO; Cryomilling; High energy density materials; Nanocomposite; Thermite